Assessing the sprint force-velocity profile in international football players with cerebral palsy: Validity, reliability and sport class` profiles - Peña-González, I.; Javaloyes, A.; Sarabia, J. M.; Moya-Ramón, M. (Journal of Human Kinetics, 2022)
This study assessed and described the Sprint Force-velocity (SFv) profile, and its validity and reliability in international cerebral palsy (CP) football players. Twenty international male CP football players (age: 26.9±7.4) performed a 30-m sprint, a vertical jump (CMJ), a change of direction (MAT), a dribbling and an intermittent endurance (Yo-YoIR1) test. The SFv profile and physical performance variables were shown according to the players` sport class with the estimation of the effect sizes between classes. The SFv showed high reliability (ICC=0.77 to 0.99; SEM=0.89 to 8.66%). Validity for the SFv was provided by its positive correlation with the players` sport class (r=0.53 to 0.75; p=.02 to <.01) and the rest of the physical performance tests (r=0.45 to 0.99; p=.04 to <.01). The RF max was the main SFv profile variable that explained players` performance in the rest of the tests (ß=0.77 to 1.0; p<.05; R2=0.59 to 0.99). The SFv profile seems to be an efficient test to assess international CP football players` physical performance. This provides information about the players` individual sprint mechanical characteristics and their sprint strengths and weaknesses, allowing coaches and conditioning trainers to individualize their training interventions to optimize sprint performance.